Implementation of Project Based Learning (PjBL) Learning Model Through Wall Magazine Towards Learning Achievement and Collaborative Skills - Dini Nur Nuha; Beta Wulan Febriana; Krisna Merdekawati (International Journal of Chemistry Education Research, 2020)
The purpose of this study is to investigate whether there are significant differences in students’ learning achievement and collaborative skills between class that implement Project-Based Learning model and the conventional learning model on the buffer solution material. This research is an experimental study that using quasi-experimental design, post-test only with non-equivalent group design. The population used in this study were all students of 10th grade by using two classes as research samples. Data were analyzed using the Independent Sample T-Test for learning achievement in knowledge, as well as the non-parametric Mann Whitney U test for students’ learning achievement and collaborative skills. The results of this study can be concluded that there are significant differences in students' learning achievement and collaborative skills between the implementation of the PjBL learning model and conventional learning models on the buffer solution material. Keywords: project-based learning, collaborative skills, learning achievement